Information System Components for Designing Financial Applications in Small and Medium Enterprises - D R Aryawibawa; D A W Syaroni (Peneliti.net, 2020)
The purpose of this study is to find out the important components that form the basis of financial information system design in helping small and medium-sized businesses manage their finances so they can develop their business to the maximum. This research used study literatures from previous research about financial information system design The result of this research is financial software that helps SMEs monitor and manage their cash flow through gadgets. Every SME needs good financial system to monitor and control their cash flow any time. Technological development nowadays could be utilized to develop it. The benefit is that SMEs can easily access their financial report through gadgets without be concerned about data damaged or data loss.